An English-Based Organizational Acronym Strategy to Enhance Meeting Management in Student Organizations: A Case Study - Ali Mohammed Saleh Al-Hamzi; Nurmala Dewi; Tati Mardewi; Furi Indriyani; Octa Pratama Putra (Wanastra: Jurnal Bahasa dan Sastra, 2026)
While mnemonic devices are widely used in educational contexts for enhancing cognitive retention, their socio-cognitive utility and structural paradoxes within organizational governance remain under-researched. This study investigates how English-based acronym strategies influence meeting management and executive behaviors among student organization leaders. Grounded in a qualitative research design, this study examines the experiential accounts of eight student leaders serving on students’s affair of the university. Data collection was conducted through in-depth semi-structured interviews, which were subsequently analyzed using an iterative thematic approach combined with conceptual lenses from applied linguistics and cognitive scaffolding. The findings reveal a compelling dualistic phenomenon. On one hand, English-based acronyms (e.g., L.E.A.D.E.R.S.H.I.P., M.A.N.A.G.E.M.E.N.T., M.A.S.T.E.R.) operate as effective cognitive scaffolds and regulatory anchors that minimize the cognitive load, stabilize conversational trajectories, and arrest discursive drift during complex deliberations. On the other hand, a critical alternative interpretation uncovers a distinct structural paradox: the efficacy of these frameworks is inversely proportional to their structural density. Extensive, high-density acronyms risk inducing operational rigidity and cognitive dependency, inadvertently transforming fluid democratic dialogues into procedural checklists or sites of discursive policing. Furthermore, shorter formulas to maximize real-time agility but face the risk of superficial ritualization, where participants perform compliance linguistically while deep-seated behavioral habits remain unaltered. This study concludes that acronym-based organizational strategies exist in a permanent tension between artificial linguistic order and organic communicative spontaneity. It implies that student executives must deploy these devices as flexible conceptual anchors rather than rigid procedural mandates to safeguard institutional resilience.